YAP/TAZ and ATF4 drive resistance to Sorafenib in hepatocellular carcinoma by preventing ferroptosis. Issue 12 (19th October 2021) - Gao, Ruize; Kalathur, Ravi K R; Coto‐Llerena, Mairene; Ercan, Caner; Buechel, David; Shuang, Song; Piscuoglio, Salvatore; Dill, Michael T; Camargo, Fernando D; Christofori, Gerhard; Tang, Fengyuan
Abstract: Understanding the mechanisms underlying evasive resistance in cancer is an unmet medical need to improve the efficacy of current therapies. In this study, a combination of shRNA‐mediated synthetic lethality screening and transcriptomic analysis revealed the transcription factors YAP/TAZ as key drivers of Sorafenib resistance in hepatocellular carcinoma (HCC) by repressing Sorafenib‐induced ferroptosis. Mechanistically, in a TEAD‐dependent manner, YAP/TAZ induce the expression of SLC7A11, a key transporter maintaining intracellular glutathione homeostasis, thus enabling HCC cells to overcome Sorafenib‐induced ferroptosis. At the same time, YAP/TAZ sustain the protein stability, nuclear localization, and transcriptional activity of ATF4 which in turn cooperates to induce SLC7A11 expression. Our study uncovers a critical role of YAP/TAZ in the repression of ferroptosis and thus in the establishment of Sorafenib resistance in HCC, highlighting YAP/TAZ‐based rewiring strategies as potential approaches to overcome HCC therapy resistance. SYNOPSIS: Resistance to therapy occurs in most liver cancer patients treated with Sorafenib, and patients succumb to the disease. A synthetic lethal screen identified a regulatory circuit, which prevents ferroptosis and promotes cancer cell survival, thus promoting resistance to Sorafenib. The transcription factors YAP and TAZ stabilize ATF4 by promoting its nuclear import to cooperatively induce expression of SLC7A11, a cystine importer critical for glutathione synthesis. Glutathione synthesis and homeostasis are required to repress ferroptosis and to maintain Sorafenib resistance in liver cancer cells. Inhibition of Glutathione synthesis re‐sensitizes Sorafenib‐resistant cancer cells to Sorafenib therapy, which then induces ferroptosis and represses tumor growth in murine liver cancer models. Pharmacological repression of the anti‐oxidant pathways regulated by YAP/TAZ and ATF4 could re‐sensitize therapy‐resistant liver cancers to Sorafenib treatment. Abstract : Resistance to therapy occurs in most liver cancer patients treated with Sorafenib, and patients succumb to the disease. A synthetic lethal screen identified a regulatory circuit, which prevents ferroptosis and promotes cancer cell survival, thus promoting resistance to Sorafenib.